Protective role of cyclooxygenase (COX) inhibitors in burn-induced intestinal and liver damage - (:unkn) unknown (My University, 2002)
The aim of this study was to investigate the role of cyclooxygenase (COX) inhibition in intestinal motility and in the extent of tissue injury of the small intestine and liver with the use of various COX inhibitors. Wistar albino rats were exposed to 90 degrees C water bath for 10s. The intestinal transit index decreased compared to control group and treatment with nimesulide (NIM; 10mg/kg, subcutaneously) or piroxicam (Pir; 5mg/kg, orogastrically) reversed this effect significantly. The intestinal and liver glutathione levels showed a significant decrease in the burn group compared to sham (P<0.001 and P<0.05, respectively). Decrease in intestinal glutathione level was reversed by NIM or Pir treatment (P<0.01 and P<0.01, respectively), whereas all drugs tested were effective in reversing low liver glutathione level. The MPO activity in intestinal segments were significantly high in burned animals compared to sham. All test drugs reversed this effect but ketorolac (Ket; 3mg/kg, orogastrically) was the most effective one. The liver samples characterized by sinusoidal dilatation and pericentral atrophy in burn group were protected by treatment with Ket or Pir (P<0.05). Plasma ALT and AST activities were markedly high in this burn group compared to sham (P<0.0001 and P<0.001, respectively). None of the agents reversed these high enzyme activities. These data suggest that not only COX-2 but also COX-1 inhibition is required for protection against inflammatory changes in liver and small intestine following burn injury.
Keywords: Animals; Rats; Rats, Wistar; Glutathione; Lipid Peroxidation; Liver; Intestinal Mucosa; Peroxidase; Burns; Cyclooxygenase Inhibitors; Intestines; Gastrointestinal Motility; Liver Function Tests